The FAKTOR RESIKO ANEMIA PADA IBU HAMIL DI UPT BLUD PUSKESMAS RUMBIO KABUPATEN KAMPAR - Dewi Anggriani Harahap (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
Anemia is the largest public health problem in the world, especially for women of reproductive age. The objective of the study was to analyze the risk factors for anemia among pregnant women in UPT BLUD Puskesmas Rumbio, Kampar. This research use analytical method with cross sectional approach. The population in this study were all pregnant women in the working area of UPT BLUD Puskesmas Rumbio periode Mei 2021, and sample of 42 people. Data analysis using univariate and bivariate analysis using distribution tables and chi square statistical test with 95% confidence interval. Statistical analysis showed a correlation between the incidence of anemia in pregnant women with gestational age (0.024), maternal interval (0.035), parity (0.016) and antenatal care (0.001).